2014
DOI: 10.1002/app.40329
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of acrylonitrile–butadiene–styrene copolymer/poly(l‐lactic acid) blends and their composites

Abstract: As the material properties of acrylonitrile-butadiene-styrene copolymer (ABS) have an excessively wide margin for applications in automobile console boxes, ABS partly replaced with poly(L-lactic acid) (PLA) may be used for the same purpose with improved ecofriendliness if the corresponding deterioration of the material properties is acceptable through the choice of appropriate additives. ABS composites with 30 wt % renewable components (PLA and cellulose pulp) were prepared by melt compounding, and the materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…The blend without additives has a very low impact strength value. This is expected, as the poor compatibility of this blend is covered in the literature . In fact, many works have started from a point of compatibilization, knowing that the neat blend has very poor performance.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The blend without additives has a very low impact strength value. This is expected, as the poor compatibility of this blend is covered in the literature . In fact, many works have started from a point of compatibilization, knowing that the neat blend has very poor performance.…”
Section: Resultsmentioning
confidence: 87%
“…found that high speed tensile testing and impact testing shared a brittle to ductile mechanism . The PLA/ABS blend, which has very low compatibility as cited in the literature, also has a very low elongation at break . This will likely also lead to low impact strength, which will be analyzed in the next section, as there is insufficient energy absorption with even low loading of the blend.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The toughness of PLA increases when it is blended with thermoplastic polyurethane (TPU) [4] , polycaprolactone (PCL) [5] , poly(butylenes succinate) (PBS) [6] , poly(butylene adipateco-terepthalate) (PBAT) [7] , acrylonitrile-butadienestyrene terpolymer (ABS) [8,9] , caprolactone/trimethyl carbonate copolymer, and caprolactone/lactide diblock copolymer [10] . Natural rubber (NR), acrylonitrile-butadiene rubber (NBR), and isoprene rubber (IR) can also improve impact strength [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Acrylonitrile–butadiene–styrene (ABS) is a copolymer of acrylonitrile, butadiene, and styrene . It has been widely used in industry because of its good physical and mechanical properties, such as impact resistance and toughness . These properties are related to the composition of the polymers.…”
Section: Introductionmentioning
confidence: 99%